Reading ideas in Victorian literature : literary content as artistic experience - Fessenbecker, Patrick (Edinburgh University Press, 2020)
Argues against the repeated emphasis on literary form and for the artistic importance of literary content.
Keywords: English literature -- 19th century -- History and criticism.; Littérature anglaise -- 19e siècle -- Histoire et critique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature; 1800-1899; Electronic books.; Criticism, interpretation, etc.